Metodología para el diseño y optimización de formulaciones oleosas estables con el uso de Montanide 888 VG. - Baryolo-González, Linnet; Pérez-Heredia, Carlos Enrique; González-Fernández, Nemecio (Revista CENIC Ciencias Quimicas, 2015)
The emulsions are used in biotechnology in the formulation of a large number of immunogens. Efforts have been devoted to study and understand these systems, but the complexity of the emulsifiers, the interaction forces and active ingredients that are used, reduce the accuracy in the prediction of stability. In the present work a study was conducted to determine the influence of phase composition, and ionic strength on the behavior of an emulsion using the Montanide 888 VG as emulsifier. Using a mixture experimental design mathematical model was adjusted, describing the influence of emulsion composition on the mechanical stability, the thermal stability, viscosity and particle size. A numeric factor for ionic strength was included. Mechanical stability was determined by centrifugation and thermal stability by accelerated test at 37 °C. Ostwald de Waele law using a rotational viscometer determined viscosity. The simulation and optimization models were developed using Matlab 7.0.1 software. Emulsifier concentration had a significant influence in the emulsion cost and in it stability. To minimize the emulsion cost, it was observed that employing a composition of 50 % aqueous phase, 47,5 % mineral oil and 2,5 % emulsifier Montanide 888 VG can be obtain a stable emulsion for the formulation of veterinary immunogens.